วิธีการและเครื่องมือการสื่อสารข้อมูลการตลาดสำหรับสถาปนิกในการออกแบบโครงการที่พักอาศัยประเภทอาคารชุด - อัญชุลีกร อุดมแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The number of commercial condominium projects is growing rapidly in Thailand and architectural design plays a part in this development. The architect has to jointly work with the project owner whose main focus is on marketing the project. As a result, the architect has to communicate effectively with the owner because designing a condominium requires knowledge in other fields such as marketing, economics and finance. At present, some architects may not have any profound understanding of such fields, resulting in conveying wrong information or omitting important information which could help improve the project. The purposes of this study are to investigate notions and theories related to the development of condominium projects, to study the process of developing condominium projects, to study marketing factors, to study location factors, to study the details of the projects and to study communication based on case studies. The research was conducted by selecting condominiums whose prices range from average to high as case studies. These condominiums are located in Bangkok and were constructed by real estate companies in Bangkok which have had experience in developing at least 3 condominium projects. The companies and the condominiums chosen as case studies had to meet specific requirements. 5 projects were chosen as case studies whose managers and architects were interviewed. In addition, a literature review was also carried out. The case studies were analyzed, concluded and assessed by an authority in designing condominium projects. It was found that miscommunication or lack of communication arises from not having enough concrete information and the sources of communication problems were both the architects and other parties. Such problems are a lack of knowledge regarding the best way to communicate, not having enough documentation to communicate, and a lack of understanding of the working procedures. Consequently, the communication should be more concrete so that each party will have the same information. The researcher has proposed methods and tools for communicating for architects to help them improve their communication. It can be concluded that to help the architect design a condominium project properly, there should be appropriate methods and tools to aid communication outside and inside organizations more effectively and more efficiently; as a result, conveying incorrect information will be reduced which will benefit both architects and the project. The methods and tools for communication were assessed by an authority in terms of the general advantages and the application. It can be said that these medhods and tools are useful and can solve communication problems about marketing for the architect who designs condominium projects.